Patrimonio immobiliare pubblico Prospettive di rigenerazione per una città accessibile e di prossimità - Ladu, Mara (Tomorrow's cities, 2022)
This volume addresses the issue of knowledge, management and enhancement of public real estate assets, within an ambitious perspective of urban regeneration consistent with the principles underlying an accessible city of proximity.